Telaah Manajemen Pendidikan Modern Dan Penerapan Manajemen Pendidikan Berbasis Sekolah - R. Nurhayati; Diarti Andra Ningsih; Kahar Kahar; Musdalifah Musdalifah; Muttiah Rahma; A. Muh. Nur Hakiki; Agus Suwito (Departement of Mathematics Education, 2023)
This study aims to describe how modern education management is implemented by schools and describe the implementation of school-based management, as well as the supporting and inhibiting factors of school-based education management. The method used in this study is a qualitative method using descriptive qualitative. The subject of this research is SMPN 7 Sinjai, while the object is the Study of Modern Education Management and Implementation of School-Based Education Management. Data collection techniques were carried out by interviews and documentation, the data collection instruments were interview sheets and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The results of this study indicate that the forms of modern education implemented by the school are using online-based learning such as using the internet in digital media, conveying material using power point, and using learning applications. Then the use of kern books and links instead of printed books. The implementation of school exams is carried out using a combination mode assisted by the exam browser application to prevent students from being dishonest in working on questions. The method used during school exams is multiple choice questions done using a computer, while essay questions are done in writing. The application of school-based education management in the teaching and learning process is that the management is returned to the school and implemented according to the agreed School Operational Curriculum (KOPS). Carry out Al-Qur'an literacy in every lesson and utilize school facilities and infrastructure. The implementation of SBM in the personal field is carried out by dividing tasks by decree, helping senior teachers who are lacking in the field of Technological Science (IT), and conducting Subject Teacher Consultations (MGMP). In School-Based Education Management (SBM) the school's relationship with the community is the school's guarantee for the safety of students to parents, carrying out a communication process to improve and develop school activities, working with the school committee and conducting friendships through outreach and meetings. supporting the implementation of School-Based Management (SBM), namely clear authority and school autonomy factors, gradual government assistance, empowerment of effective educational facilities, good school culture and Human Resources (HR), as well as responsible school committees and good organizational leadership. Good. The inhibiting factors are if there is no communication and cooperation between school environments, as well as inadequate facilities, such as an insufficient number of computers with a number of students and wifi or uneven network in all classes.